2009
DOI: 10.1039/b915448p
|View full text |Cite
|
Sign up to set email alerts
|

Rapid formation of complexity in the total synthesis of natural products enabled by oxabicyclo[2.2.1]heptene building blocks

Abstract: This critical review showcases examples of rapid formation of complexity in total syntheses starting from 7-oxabicyclo[2.2.1]hept-5-ene derivatives. An overview of methods allowing synthetic access to these building blocks is provided and their application in recently developed synthetic transformations to structurally complex systems is illustrated. In addition, the facile access to a novel oxabicyclo[2.2.1]heptene derived building block is presented which significantly enlarges the possibilities of previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…The intramolecular Diels–Alder reaction on furans (IMDAF reaction) allows the formation of two or more rings in a single step, often with high regio‐ and stereochemical control 1. The initially formed oxanorbornene ring system can easily be converted into other cyclic structures,2 and the IMDAF reaction is often applied in synthesis directed towards natural products and ring systems found in nature 3,4. We have previously shown that allylamino‐ or allyloxyfuryl(hetero)arenes can undergo IMDAF cycloaddition to give complex fused polycyclic heterocycles 5.…”
Section: Introductionmentioning
confidence: 99%
“…The intramolecular Diels–Alder reaction on furans (IMDAF reaction) allows the formation of two or more rings in a single step, often with high regio‐ and stereochemical control 1. The initially formed oxanorbornene ring system can easily be converted into other cyclic structures,2 and the IMDAF reaction is often applied in synthesis directed towards natural products and ring systems found in nature 3,4. We have previously shown that allylamino‐ or allyloxyfuryl(hetero)arenes can undergo IMDAF cycloaddition to give complex fused polycyclic heterocycles 5.…”
Section: Introductionmentioning
confidence: 99%
“…In the synthesis of Banyaside, we discovered a remarkably mild process for the opening of oxabicyclic ring systems by amines . In the specific study, we observed that oxabicycloheptanes participated in intramolecular ring‐opening reactions, furnishing hexahydroindoles and perhydroquinolines . The fact that the transformation proceeds under remarkably mild conditions does not fail to amaze me, even many years after we disclosed our study.…”
Section: Introductionmentioning
confidence: 70%
“…We recently reported a nine‐step synthesis of the Abn core 4. 5 Herein, we disclose studies focused on the side‐chains. These studies have led to an approach for the installation of a hindered peptide along with O‐sulfation, and glycosylation reactions.…”
Section: Methodsmentioning
confidence: 99%